Implementasi Wirausaha Budidaya Ternak Kambing Studi di Panti Asuhan Rukun Santosa Kencong - M Ahksin Rohmatullah; Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
This research we conducted in the orphanage Rukun Santosa Kencong Kediri with a focus on the study of the management of goat enlargement, the development of independence of the students under the auspices of the orphanage, additional sources of funds for the institution. The purpose of this research is our consideration in starting the cultivation of goat livestock. Data collection through interviews from one of the students of the orphanage who served as the manager of a business entity owned by the orphanage foundation, direct observation in the orphanage and analysis of the phenomenon that we found.